Structural and optical properties of MBE‐grown asymmetric cubic GaN/AlxGa1–xN double quantum wells. Issue 5 (17th December 2014) - Wecker, T.; Hörich, F.; Feneberg, M.; Goldhahn, R.; Reuter, D.; As, D. J.
<x xml:space="preserve">Abstract</x> The non‐resonant carrier transfer in asymmetric double quantum wells is studied. Asymmetric cubic GaN/AlxGa1−xN double quantum wells with Al content of x = 0.26 ± 0.03 were grown on 3C‐SiC (001) substrate by radio‐frequency plasma‐assisted molecular beam epitaxy. The barrier thickness d between a wide quantum well having 2.5 nm thickness and a narrow quantum well with width of 0.7 nm was varied from 1 to 15 nm. Furthermore, high resolution X‐ray diffraction reciprocal space maps around the (113) direction provided the Al content and revealed a partially strain in the AlxGa1−xN barriers and QWs. The coupling between the QWs was studied by interband photoluminescence spectroscopy at low temperatures. Four clearly distinguishable emission bands at 3.27 eV, 3.37 eV, 3.60 eV, and 3.74 eV are observed and could be assigned to the different layers. With decreasing barrier thickness d the photoluminescence intensity from the narrow QW is strongly reduced, indicating wave function redistribution from the narrow QW to the wide QW. The emission energies for the QWs are in good agreement with theoretical calculations using a Schrödinger–Poisson solver based on an effective mass model (nextnano3). The PL intensity ratio of the narrow QW to the wide QW for varied barrier thicknesses was calculated by exploiting rate equations, revealing a good agreement between theory and experiment.